Investigation of mobile genetic elements and their association with antibiotic resistance genes in clinical pathogens worldwide. - Markus H K Johansson; Thomas N Petersen; Sidsel Nag; Timmie M R Lagermann; Laura E K Birkedahl; Silva Tafaj; Susan Bradbury; Peter Collignon; Denise Daley; Victorien Dougnon; Kafayath Fabiyi; Boubacar Coulibaly; et al. (PLoS ONE)
Objectives Antimicrobial-resistant bacteria are a major global health threat. Mobile genetic elements (MGEs) have been crucial for spreading resistance to new bacterial species, including human pathogens. Understanding how MGEs promote resistance could be essential for prevention. Here we present an investigation of MGEs and their association with resistance genes in pathogenic bacteria collected from 59 diagnostic units during 2020, representing a snapshot of clinical infections from 35 counties worldwide. Methods We analysed 3,095 whole-genome sequenced clinical bacterial isolates from over 100 species to study the relationship between resistance genes and MGEs. The mobiliome of Staphylococcus aureus, Enterococcus faecalis, Escherichia coli, and Klebsiella pneumoniae were further examined for geographic differences, as these species were prevalent in all countries. Genes potentially mobilized by MGEs were identified by finding DNA segments containing MGEs and ARGs preserved in multiple species. Network analysis was used to investigate potential MGE interactions, host range, and transmission pathways. Results The prevalence and diversity of MGEs and resistance genes varied among species, with E. coli and S. aureus carrying more diverse elements. MGE composition differed between bacterial lineages, indicating strong vertical inheritance. 102 MGEs associated with resistance were found in multiple species, and four of these elements seemed to be highly transmissible as they were found in different phyla. We identified 21 genomic regions containing resistance genes potentially mobilized by MGEs, highlighting their importance in transmitting genes to clinically significant bacteria. Conclusion Resistance genes are spread through various MGEs, including plasmids and transposons. Our findings suggest that multiple factors influence MGE prevalence and their transposability, thereby shaping the MGE population and transmission pathways. Some MGEs have a wider host range, which could make them more important for mobilizing genes. We also identified 103 resistance genes potentially mobilised by MGEs, which could increase their transmissibility to unrelated bacteria.